Substantiation of Value Oriented Management Changes of State Seaport - Mickienė, Rima; Valionienė, Elena (Socialiniai tyrimai, 2018)
Efficient operations of state enterprises play a significant role in promoting development and growth of the national economy, and accordingly require implementing the most efficient model of governance. Given the state-seaport relation, current common concepts of port operations and their factors include features of Keynesian economic theory. Moreover, features of monetarism and institutionalism may be observed in the performance of seaports. The contrast between the assessment of seaport performance based on classical public administration and economic theories and the performance of the global maritime sector in modern market conditions raises the scientific problem of the research: Which methodology should be applied for comprehensive evaluation of added-value, created through the effective governance at the state seaport. The object of the research is the seaport governance. The aim of the research is to substantiate value oriented management changes of state seaport. The methods of the research include the following: systematic review, meta-analysis, analysis of scientific literature, logography, statistical analysis, interpretation, and generalization.Effective management consists of the following three managerial levels: operational management, strategical management, and governance. Each of latter management levels has different functional objectives and their consistent implementation creates the expected outcomes of effective management. The activities of state-owned companies are primarily based on their specific operational indicators, which create added value to the whole national economy. In order to achieve the highest possible added value, different management situations have to be modelled for the best solution to be found. According to the theory of public administration, especially related to the decentralization of state-owned enterprises, it is necessary to compare the indicators of financial efficiency and performance with the social and economic impact of the state-owned enterprises operating in the competitive market and region. The decentralization processes which occur due to the implementation of financial and institutional autonomy were implemented during the development of the new public management paradigm. At the end of the last century, many public management reforms were implemented in the area of infrastructure, transport and telecommunication management following the increase of the financial and institutional autonomy of state-owned enterprises. Such reforms were influenced by the shift of bureaucratic governance into corporate governance and following an increase of competitiveness in the market.Determining the effectiveness of seaport governance may indicate the level of complexity and linkages between the actors operating in the seaport and whole maritime transport sector. Moreover, the effectiveness of state-owned seaports may be evaluated and compared to other governance models by assessing the added value of activity and national socio-economic indicators. Economic theories provide a large variety of methodological approaches in defining and assessing performance. This responds to the tendency of the development of economic thought, related to the key differences between current economic schools and economic theory (postmodernist, free market, neoclassical, endogenous growth, etc.). It also promotes the need for forming a new research methodology, corresponding to modern economic development and operating environment, in order to reach a greater production and exchange efficiency, and social welfare maximization.In the eastern coast of the Baltic Sea, the ports of Estonia, Latvia and Lithuania compete with the ports of the Russian Federation. Comparing the main port activity indicator, the volume of cargo handling, the apparent trend of turnover of Lithuanian ports – cargo handling rate is lower than of the ports of the Russian Federation and is the largest in the Baltic states market. Based on the analysis of the results of Estonian, Latvian and Lithuanian ports, it can be argued that the positive and consistent improvement of the performance of the strategic object of the country, the state seaport, is a significant but insufficient indicator describing the country’s social, economic and environmental situation. This confirms the theoretical statements that good macroeconomic indicators of various sectors of the state economy are not a precise unit of measurement of the current situation, do not adequately describe the actual economic situation of the country and do not meet the expectations of the population. In order to reflect the real socio-economic situation, it is necessary to follow the systematic conception of quality of life, which interprets the quality of life of the population as an integrated concept that fully describes the ecological, economic, material and moral health of society, measured at the macro level (national scale) and micro level (from the point of view of an individual).
Keywords: added value oriented management; public management; seaport governance; seaport economics; quality of life economics